Digital Transformation and Work Culture Change in Public Administration: Evidence from Indonesia - Hairul Yunas Sanduan; Jusuf Madubun; Aminah Bahasoan (Jurnal Ilmiah Global Education, 2026)
This study investigates the impact of digitalization on civil servants’ work culture at the Class I Navigation District of Ambon, addressing a gap in the literature regarding the integration of New Public Governance (NPG) principles with technology adoption in geographically fragmented public institutions. The urgency of this research is underscored by the operational context of high-risk maritime environments, where effective service delivery is critical for safety and organizational reliability. Using a qualitative case study design, data were collected over three months through semi-structured interviews, participant observation, and document analysis with 15 purposively selected informants across generational and hierarchical groups. Triangulation ensured methodological rigor, while interactive data analysis allowed themes to emerge inductively and in alignment with theoretical frameworks. The study applies the Technology Acceptance Model (TAM) and the ADKAR change model to interpret both psychological and procedural aspects of digital adoption. Findings indicate that digital systems, including AIS, MaritimHUB, E-Kinerja, SIK, SRIKANDI, E-Correspondence, SIMAN, and SAKTI, have significantly transformed operational and administrative work culture, enhancing efficiency, transparency, and accountability. Top-down directives combined with structured training facilitate adoption, yet barriers such as uneven system use, digital literacy gaps, and infrastructure limitations remain. Aligning technological implementation with organizational change and collaborative governance principles is critical for sustaining effective digital transformation. The study recommends continuous capacity-building, infrastructure improvements, and integrated application management to strengthen digital work culture and service quality.